Amelogenin and alkaline phosphatase expression in ameloblast after saltwater fish consumption in pregnant mice (Mus musculus) - Christiono, Sandy; Pradopo, Seno; Sudiana, I Ketut; Hutami, Islamy Rahma; Mayangsari, Regilia Shinta; Rochmah, Yayun Siti; Ibrahim, Zurairah (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: The intricate process of tooth formation during embryonic development ensures sufficient nutrition for the growth of healthy dental tissues. Amelogenin and alkaline phosphatase (ALP) are serine proteinases secreted by the ameloblast during the transition and maturation phases of the amelogenesis process. Consumption of saltwater fish is predicted to increase the expression of amelogenin and ALP in ameloblast cells during tooth formation. Only now have the function of each gene, tooth-forming cells, and the proteins they produce in the biomolecular amelogenesis of tooth enamel, which began during prenatal development, been clarified. Purpose: This study aims to determine how saltwater fish powder affects the ability of mother mice to increase the expression of amelogenin and ALP in cell ameloblast. Methods: Using a completely randomized design, this study was experimental and aimed to examine the effects of sardine (Sardinella fimbriata), splendid ponyfish (Leiognathus splendens), and tuna (Euthynnus affinis) powder. As samples, twenty-four female mice (Mus musculus) were used. Two groups of mice were created: group 1 (2.14 mg/0.5 ml) and the control group. The expression of amelogenin and ALP was determined using immunohistochemistry (IHC) and t-test (p0.05). Results: Expression of ameloblast was significantly different between the treatment and control groups (p0.05). Conclusion: The consumption of saltwater fish reduces the amelogenin and ALP expressions of mouse fetal ameloblast cells during tooth development in vivo.